Border Tourism: a Synergicity Model of Economic Empowerment Program in Overcoming Social Economic Inequalities in the Indonesia Land Border Region-Malaysia - M. Irfani Hendri; Hasanudin Hasanudin; Vitriyan Espa; Juanda Astarani (Journal Research of Social Science, Economics, and Management, 2022)
Poverty and socio-economic disparities in the border areas in West Kalimantan are the most conspicuous issues. But on the other hand, the border area has very rich natural resources but has not been utilized/exploited optimally. This study aims to describe the potential of the Indonesia-Malaysia land border area in Sajingan Besar District and Paloh District (PALSA) in Sambas Regency then a synergy model of economic empowerment program for border area communities will be developed. The approach used in this research is a qualitative approach and this type of research is a case study. For the purposes of analysis, data collection uses triangulation data collection methods which include observation, interviews and documentation. Based on the research results, several programs that synergize with economic empowerment programs include: a) Entrepreneurship Program for prospective new entrepreneurs; b) Business incubator establishment program at each university; c) village incubator program based on village superior products; d) Business development service program (village/kelurahan); e) BUMDes program based on village innovation and f) Leverage program: MSME big house tourism.